Realization of Friction Stir Welding of Aluminum Alloy AA5754 Using a Ceramic Tool - Toni Sprigode; Andreas Gester; Guntram Wagner; Ulrich Degenhardt (Metals, 2024)
When engaging in the friction stir welding of aluminum/aluminum joints, the conventional use of tools made of hard metal and steel involves a complex and costly production process. These tools experience wear over welding distances and require frequent replacement to ensure the consistency of the welded seams. The exploration of silicon nitrite as a tool material emerges as a promising alternative in this scenario. The heightened hardness of non-oxide ceramics anticipates a diminished wear rate compared to traditional welding materials, translating into an extended operational lifespan. Nevertheless, the adoption of ceramics introduces challenges initially perceived as detrimental to friction stir welding. The inherent brittleness of silicon nitrite makes it susceptible to breakage under specific loads, and thermal stresses within the component can lead to failure. To mitigate these vulnerabilities, a ceramic material with high thermal shock resistance and a low proportion of sintering additives was used. Employing these accurately designed tools friction stir welding (FSW) was performed on sheets of AA5754, followed by a comprehensive examination of their microstructural and mechanical properties. It was demonstrated that a joint efficiency of 88% can be achieved, and that an increase in hardness within the stir zone occurred as a consequence of grain refinement. Furthermore, the Portevin–Le Chatelier effect, which is characteristic of this alloy, was influenced by the FSW process.